The effect of fluid shear stress on fibroblasts and stem cells on plane and groove topographies. Issue 1 (1st January 2020) - Lei, Xing; Liu, Bin; Wu, Hao; Wu, Xiao; Wang, Xiu-Li; Song, Yue; Zhang, Shuai-Shuai; Li, Jun-Qin; Bi, Long; Pei, Guo-Xian
ABSTRACT: In this study, we aimed to study the effect of fluid shear stress on fibroblasts and BMSCs on plane and groove topographies. The results showed that 0.6-Hz stress had the greatest influence on the alignment, polarity, migration and adhesion of fibroblasts on plane by increasing the expression of reoriented actin and vinculin; whereas 1.0-Hz stress promoted differentiation of fibroblasts into myofibroblasts by increasing Col-I and α-SMA expression. Interestingly, under the given frequency stress, the groove structure strengthened the above characteristics of fibroblasts beyond adhesion, and promoted differentiation of BMSCs into myofibroblasts. The above results indicate that 0.6 Hz may improve the implant-tissue sealing, while 1.0-Hz stress probably causes the disordered fiber deposition around implants.